TYPES OF INFECTIONS: PATHOPHYSIOLOGY AND CLINICAL IMPLICATIONS - Razhabova Zebiniso Safarovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Infections  are  caused  by  various  pathogens,  including  bacteria, viruses, fungi, and parasites, leading to diverse clinical manifestations. Understanding the different types of infections, their pathophysiological mechanisms, and their impact on human health is essential for effective diagnosis and treatment. This article explores the  classification  of  infections,  their  modes  of  transmission,  and  management strategies.